1373. Vaccine Effectiveness and Pneumococcal Serotypes in Pediatric Otitis Media in the Era of Routine 13-valent Pneumococcal Vaccination in the United States. (31st December 2020) - Hulten, Kristina G; Barson, William; Lin, P Ling; Bradley, John S; Peters, Timothy R; Tan, Tina Q; Romero, Jose R; Pannaraj, Pia S; Kaplan, Sheldon L
Abstract: Background: Pneumococcal acute otitis media (AOM) in children due to vaccine related serotypes (St) declined after the introduction of the 13-valent pneumococcal conjugate vaccine (PCV13). Methods: Patients < 18 years with pneumococcal OM isolates from 2014-2019 from the U S Pediatric Multicenter Pneumococcal Surveillance Group were analyzed for demographics, immunization status, antimicrobial susceptibility and St distribution. p< 0.05 was considered statistically significant. Vaccine effectiveness (VE) was calculated using a standard formula: 1-([PCV13St vaccinated (≥3 PCV13 doses) x Non-PCV13St unvaccinated (0-1 PCV13 doses)]/[PCV13St unvaccinated x Non-PCV13St vaccinated]) Results: 646 patients were identified. Patients with PCV13 St were older compared to patients with non-PCV13 serotypes (3.3 vs 1.5 median years, p< 0.0001). Most isolates were from spontaneous drainage (71.4 %) and PE tube placements (26.9%). 36 different Sts were identified; 83.4% of isolates were non-PCV13 Sts; 35B represented 18.3% of all isolates. St 19A decreased over time (p=0.0003). 14% of isolates had penicillin MIC ≥2 µg/ml and 2.4% had ceftriaxone MIC >1 µg/ml. (Figure) 633 patients had known vaccine status. VE was 86.4% (Table). Table. Conclusion: Non-PCV13 Sts caused most pneumococcal OM. St35B was the most common St. St 19A decreased as a cause of otitis. In this study the VE of≥3 PCV13 doses was 86% for pneumococcal OM. Disclosures: Tina Q. Tan, MD, Pfizer (Grant/Research Support, Other Financial or Material Support, Chair, DMSB for PCV20 vaccine) Pia S. Pannaraj, MD, MPH, AstraZeneca (Grant/Research Support)Pfizer (Grant/Research Support)Sanofi Pasteur (Advisor or Review Panel member) Sheldon L. Kaplan, MD, Allergan (Research Grant or Support)Pfizer (Grant/Research Support)